Productivity and cost of whole-tree and tree-length harvesting in fuel reduction thinning treatments using cable yarding systems - Han, Sang-Kyun; Han, Han-Sup (Forest science and technology, 2020)
Cable yarding systems are often used to reduce hazardous fuels in dense overstocked forest stands on steep terrain (>35%) in the western United States. However, treatment costs tend to be high. The aim of this study was to broaden our knowledge by evaluating two different harvesting methods (whole-tree (WT) and tree-length (TL)) used for fuel reduction thinning treatment on mixed-conifer forest stand. Different harvesting methods greatly affected the productivity and cost of fuel reduction thinning, especially in felling and yarding operations. Total sawlog removal costs (stump-to-truck) were US$26.13/m 3 in the WT-harvested unit and US$24.01/m 3 in TL harvested unit. TL thinning resulted in higher felling time and lower production rate due to increased amounts of time for processing trees at the stump. In yarding operation, however, TL method had a higher production rate than WT method because TL method had higher number of pieces per yarding cycle. Processing production rates at a landing were relatively similar throughout treatments although trees in a TL thinning unit were already limbed and bucked at the stump. Loading productivity was consistent throughout treatments because loading occurred independently from other activities. For fuel reduction thinning treatments using a cable yarding system, TL thinning was more cost-effective than WT thinning if leaving tree tops and branches on site is acceptable from a fuels management perspective.